SOCIAL MEDIA – A NEW TOOL IN MODERN ERA MARKETING (International Journal of Engineering Sciences & Management Research, 2014)
In modern era everything is online. Internet is the part of everyone’s daily life. India has third largest internet users in the world after the US and China. Social media is playing an important role in today’s era. Few years back it was not so admired, but now a day it has changed the market scenario of businesses. People like to be more online rather than offline. Marketers also know this thing .Earlier promoting the products for any Marketers were too Tuff and costly, but now with the emergence of social media businesses and organizations have got a new way by which they can promote their product and services with the maximum reach and minimum cost. Now traditional media have replaced by social media. Various social networking sites are used by marketers for promoting their products. This paper is an attempt to review/ enlighten the role of social media for marketers. The objective of this research paper is to explore the potential of social networking sites to be utilized as an effective marketing tool in engaging consumers to participate in marketing. This paper is trying to analyze the relevance of social media sites for marketers. This paper is also trying to enlighten some social media tools for marketers to promote their businesses